Control of pink discoloration in coconut water - D. B. Masa (International Coconut Community, 2007)
The pink discoloration in coconut water is a result of the initial enzymatic action of polyphenol oxidase (PPO) on the phenolic substrates which are naturally present in the product. Activity of the enzyme is further enhanced by metal contamination such as copper and exposure of the product to high temperature during its processing and storage. The optimum copper concentration to initiate pinking in coconut water was established at 3.96 x 10-04 mM. The PPO level was also shown to vary among coconut varieties and ages. When subjected to optimum conditions for enzymatic activity, the water from younger nuts (7-8 months old) went pink while mature nuts (9-10 months old) showed no discoloration. Application of food-grade resins to remove the phenolic substrates in coconut water was deemed as a possible solution to prevent the discoloration. Further testing in this area needs to be done.